Navigating Global Challenges and National Interest: The Discourse of Indonesian President Joko Widodo at the 2022 G20 Summit - Maksum, Ali; Alimuddin , Sitti Zarina; Sahide, Ahmad (Thammasat Review, 2024)
The 2022 G20 Summit marks a pivotal moment for Indonesia, traditionally seen as a regional leader, to assert its global leadership amidst domestic challenges. This article argues that as the Chairman of the 2022 G20 Summit, Indonesian President Jokowi set a crucial agenda in his opening speech. Initially, he emphasized collective action, urging member countries to address global challenges collaboratively. However, upon closer examination, his narrative reveals a primary focus on advancing Indonesia’s national interests within the context of global issues. Specifically, these interests promoted a green economy and attracted investments in renewable energy, sustainable infrastructure, and environmentally friendly industries. This perspective is reinforced not only through Jokowi’s personal words but also through statements made by his ministers. Utilising NVivo 12 Plus, a detailed discourse analysis was conducted on President Jokowi’s address at the 2022 G20 Summit. This research builds on previous studies on narratives in international relations (IR), identifying gaps related to the interplay between global leadership communication and national interests. The findings highlight Jokowi’s pragmatic diplomatic style, which balances global collaboration with national priorities, thereby contributing to a deeper understanding of the dynamics of international collaboration and responsibility.